2021
DOI: 10.47599/bsdg.v16i2.326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pendahuluan Potensi Underground Coal Gasification Di Cekungan Sumatra Selatan: Studi Kasus Batubara Formasi Muara Enim

Abstract: Salah satu cara memanfaatkan batubara bawah permukaan adalah dengan cara mengonversinya ke dalam bentuk gas yang lebih ramah lingkungan melalui metode underground coal gasification (UCG). Cekungan Sumatra Selatan adalah salah satu cekungan batubara produkfif di Indonesia. Kegiatan evaluasi ini bertujuan untuk untuk mengetahui lokasi potensi batubara yang cocok untuk pengembangan UCG. Evaluasi potensi batubara Indonesia untuk pengembangan UCG di cekungan ini, dilakukan dengan cara mengarakterisasi lapisan batub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Site selection is something very important in the UCG analysis by considering the thickness and depth of the coal seam, coal rank and other properties [7], roof and floor rock, structural geology of the area, calorific value, depth to thickness ratio, and the dip angle of the seam itself. Our study refers to Dwitama et al (2021) [8] which summarized the UCG criteria as shown in Table 2. The UCG technology will convert the solid coal into gas in situ by injecting air or oxygen.…”
Section: Underground Coal Gasification and Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Site selection is something very important in the UCG analysis by considering the thickness and depth of the coal seam, coal rank and other properties [7], roof and floor rock, structural geology of the area, calorific value, depth to thickness ratio, and the dip angle of the seam itself. Our study refers to Dwitama et al (2021) [8] which summarized the UCG criteria as shown in Table 2. The UCG technology will convert the solid coal into gas in situ by injecting air or oxygen.…”
Section: Underground Coal Gasification and Characterizationmentioning
confidence: 99%
“…The UCG technology will convert the solid coal into gas in situ by injecting air or oxygen. This injection will ignite the coal and flows in the targeted coal seam or surrounding rocks that increase temperature, pressure, and gas content as the oxygen is continuously injected and let the high-pressure gas ascend along the borehole which is known as the gasification process [7][8][9][10]. This gasification process can be optimal if we gasify the low-rank coal as it will assist in the reduction of carbon emissions due to the chemical and physical transformation [9,[11][12][13].…”
Section: Underground Coal Gasification and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations